Australia in three books ... - Flynn, Eugene (RMIT University, 2024)
BACKGROUND: Indigenous writer-scholars such as Jeanine Leane, Alison Whittaker and Evelyn Araluen have critiqued non-Indigenous engagement with Indigenous literature, both within academia and within the Australian literary sector. In her essay Cultural Rigour: First Nations Critical Culture for Sydney Review of Books, Leane (2023) writes “We…find ourselves in a time when there are a growing number of Blak literary scholars and critics, yet the dearth of Blak-on-Blak literary criticism published is striking." My research question is: ‘As an Indigenous writer-scholar, how do I ground my literary critique in Indigenous ways of knowing, being and doing?’ CONTRIBUTION: ‘Australia in three books’ is an essay of literary criticism which engages with two books by Indigenous writers and one by a non-Indigenous writer of colour (Robert Walker’s Up, not Down, Mate! Thoughts from a Prison Cell (1981); Alexis Wright’s, Carpentaria (2006); Tracey Lien’s, All That’s Left Unsaid (2022)). It forms part of my ongoing research ...